What do you do with a problem? - Yamada, Kobi.; Besom, Mae (Seattle, WA : Compendium, 2016)
When a problem becomes too big from worrying about it, a child decides to face the problem and learns that problems can make us stronger.
Kirkus Review
Publishers Weekly
Kirkus Review, April 2016
Publishers Weekly, April 2016
2.2
K-3
Keywords: Creative ability -- Juvenile fiction; Problem solving -- Juvenile fiction; Creative ability -- Fiction; Problem solving -- Fiction; Creative ability -- Fiction; Problem solving -- Fiction; Picture books